Mechanisms of impairment in hair and scalp induced by hair dyeing and perming and potential interventions - He, Yongyu; Cao, Yu; Nie, Binji; Wang, Junpu (Frontiers in Medicine, 2023)
With the rapid growth of beauty and personal care industries, many hair-relevant products, hair dyes, and hair perms, in particular, are increasingly prevalent in both women and men as they frequently change hair color or shape to enhance youth and beauty and to follow fashion trends. Hair dyes and perms alter hair color and/or shape by mechanically changing the physical structure and chemical substances of the hair shaft. However, treatment of hair with chemical formulations has been potentially ascribed to adverse outcomes in the hair shaft including structure damage, chemical constituent disorder, and impaired physical properties, though hair cosmetics procedures are intrinsically safe. Nevertheless, the mechanisms of impairment in the hair shaft and scalp induced by hair dyeing and perming remain elusive. Additionally, adverse reactions activated by exposure to specific chemical ingredients including skin irritation, allergic contact dermatitis(ACD), and even cancer risk are reported clinically, but existing evidence is not consistent enough in the case of human studies. Herein, the review aims to make an overview of hair cosmetics, especially concerning the basic knowledge about various hair dyes and perms, the consequences of hair shafts and scalp resulting from the application of hair cosmetics mentioned above, mechanisms of hazardous outcomes, and potentially desirable interventions to alleviate the impairment.